Comparison of EMG activity between single-leg deadlift and conventional bilateral deadlift in trained amateur athletes - An empirical analysis - Diamant, W. P.; Geisler, S.; Havers, T.; Knicker, A. (International Journal of Exercise Science, 2021)
The purpose of the study was to compare the normalized-electromyographic (NEMG) activity of the gluteus maximus (GMAX), gluteus medius (GMED), biceps femoris (BF) and erector spinae (ES) muscles during the single-leg deadlift (SLDL) and the conventional-deadlift (DL). Additionally, a potential influence of body height on the NEMG activity was examined. Fifteen training-experienced male subjects completed the study. SLDL showed significantly higher average concentric NEMG values of the GMED (77.6% vs. 59.3% [p = 0.002, ES = 1.0]) and BF (82.1% vs. 74.2% [p = 0.041, ES = 0.6]). Significantly lower NEMG levels were found only in the left strand of the ES muscle (67.2% vs. 82.7% [p = 0.004, ES = 0.9]). A significant influence of body height on EMG activity was also observed for all muscles, with the exception of the GMED, during the SLDL. Body height correlated negatively with the concentric EMG activity of the ES (r = -0.54 to -0.58), the BF (r = -0.63) and the GMAX (r = -0.85). In the DL there was a negative correlation only in the BF (r = -0.59) and the GMAX (r = -0.7). This means that subjects with a lower body height showed a higher NEMG activity in corresponding muscles. The results of this study indicate that the SLDL is preferable to the DL in training the BF, and GMED. In addition, coaches should be aware that athletes body height can influence the extent to which the respective muscles are activated.